Regional Spatial Regulation in Riau Province: Policy Formation Problems and Solutions - Suparto, Suparto; Santos, Jose Gama (Journal of Law, Environmental and Justice, 2024)
Regional Regulations (Perda) are statutes enacted by the Regional Head and DPRD that govern the welfare and utility aspects of the region. The Regional Spatial Planning (RTRW) rule is a crucial local ordinance that governs land allocation according to specified functions throughout various regions. The formulation of a Provincial Spatial Planning Regulation is significantly more intricate than other rules, necessitating the consideration and integration of diverse interests and the participation of several institutions, as demonstrated in the development of the Riau Provincial Spatial Planning Regulation. Following an extensive process, the Governor of Riau promulgated Regional Regulation (Perda) No. 10/2018 concerning the Regional Spatial Plan of Riau Province, with the subsequent particulars: 1. Area under cultivation measures 8,067,344 hectares. The protected region encompasses 945,532 hectares of a total expanse of 9,012,876 hectares. Despite the Regional Regulation concerning the Regional Spatial Plan and establishing the Regional Regulation on the Regional Spatial Plan of Riau Province, some concerns persist, specifically the clearance of land allocated for oil palm plantations within forested regions or for reforestation initiatives. This is difficult as it necessitates the deforestation of hundreds of thousands of hectares of oil palm plantations. Consequently, if executed meticulously, this will safeguard the ecosystem, particularly in the lack of legislation governing the restoration of land formerly converted to oil palm farms. The Government should promptly establish an implementing regulation as the legal foundation for oversight, preferably in the form of a presidential regulation